Special Education Combined with Sensory Integration Training for Children with Autism Spectrum Disorder - Ya SHAN; Min ZHU (康复学报)
Objective:To investigate the clinical effect of special education combined with sensory integration training on children with autism spectrum disorder (ASD).Methods:A total of 100 ASD children in the department of rehabilitation medicine, Children's Hospital affiliated Nanjing Medical University were randomly assigned to the special sensation group and the single special group by random number table method, with 50 cases in each group. The single special group was given special education intervention, the children should be intervened according to the special education curriculum, including the positive and negative reinforcement, systematic desensitization, extinction, temporary isolation and retribution. We would choose appropriate disgust, warning and other stimuli to minimize the incentives for bad behavior in children with negative reinforcement. For the children with positive reinforcement, we would choose effective reinforcement and gradually depart from the reinforcement process, after education, family members of the children should be guided to intervene at home according to the given intervention operations, which were synchronized with treatment, 40 minutes each time, 6 times a week, 3 months as a course of treatment. The special sensation group was given sensory integration training on the basis of the special education intervention, the personalized sensory integration training program was developed according to the condition, social ability and development of ASD children, which was included the training of tactile, vestibular and proprioceptive sensory, 2 hours each time, 3 times a week, 3 months as a course of treatment. Before the treatment and after 3, 6 months treatment, the children's autism was assessed by children's autism rating scale (CARS), the children's behavior was assessed by children's autism behavior scale (ABC), the children's therapeutic efficacy was assessed by autism treatment evaluation checklist (ATEC).Results:There was no significant difference in the CARS score, ABC score and ATEC score between the two groups before the treatment (P> 0.05); after 3 and 6 months of treatment, the CARS score, ABC score and ATEC score in the two groups were significantly lower than those before the treatment; after 3 and 6 months of treatment, the degree of decrease of CARS score, ABC score and ATEC score in the special sensation group were significantly more than those in the single special group (P< 0.05). After 6 months of treatment, the effective rate in the special sensation group (84.00%) was significantly higher than that in the single special group (64.00%), and the difference was significant (P< 0.05).Conclusion:Special education combined with sensory integration training can effectively improve ASD children's autistic degree and behavior state, and improve the therapeutic effect on children, which is worthy of further clinical promotion.